REPRESENTASI KUERI SPASIAL WARNA DENGAN LOGIKA FUZZY PADA SISTEM PEROLEHAN CITRA - M Rahmat; Widyanto Maria; Susan Anggreainy (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2009)
Image acquisition system is a field of research that flourished along with the growing number of number of is a collection of images. Zoran has developed an image acquisition system using low-level attribute that is spatial color. But the system is still found a deficiency of the approach used is crisp, with this approach there are images that are relevant but the image is not obtained, which should be obtained. In this paper fuzzy logic is proposed as an approach to represent the spatial color of the system image acquisition. Fuzzy membership functions are proposed to model the spatial gaussian two colors are in - dimensions (2D). Experiments carried out with the image data 760 by using the domain name database by category painting abstract. Test results showed that this system successfully to improve the previous approach of represent - spatial query sentasikan color. This system can provide a more natural queries to the user.